How Gut Microbiota Supports Immunity, Growth and Development of Preterm Infants: A Narrative Review - Ariani Dewi Widodo (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
ABSTRACTBackground: Gut microbiota, a complex ecosystem consisting of abundant microorganisms, plays a role in preterm infants’ immunity, growth, and development. Dysbiosis or disruption of the gut microbiota can precipitate various diseases, such as allergy or autoimmune disorders in premature infants. Purpose: This study aimed to review gut microbiota in preterm infants and its role in supporting the infants’ immunity, growth, and development. Discussion: Bifidobactericeae is the predominant microbiota in GI tract of preterm infants. However, various factors can influence this gut microbiota e.g., genetics, lifestyle of the mothers (smoking, diet, use of antibiotic, obesity), birth mode, type of feeding, and environmental factors. Gut dysbiosis can result in impaired immune system which predisposes the preterm infants to infections, even fatal adverse event. Furthermore, the growth and development might be affected as well as lead to various neurodevelopmental and psychiatric disorders. Human milk is a prebiotic source which can stimulate the growth of Baifidobactericeae and Bacteroidetes. If the human milk is inadequate or unavailable, the recommended interventions for gut dysbiosis in premature infants are probiotics, prebiotics, or both supplementations (synbiotics). The administration of prebiotics and probiotics associates with lower morbidity and death rates in preterm infants, as well as shorter duration of hospital stay and duration to achieve full enteral feeding. Conclusions: Immunity as well as growth and development of preterm infants are affected greatly by gut microbiota The less diverse microbiota in preterm infants’ gut predispose them to various health problems. Hence, this problem should be managed properly, one of which is prebiotic and probiotic supplementation Keywords: Gastrointestinal Microbiome, Premature, Immunity, Growth, Development